THE PERCEPTION ON USING DARK JOKES IN STUDENT DAILY CONVERSATION - Dameria Magdalena Sidabalok; Harpain Harpain; Sulthan Aldes Ishlah Prananca (Universitas Bandar Lampung, 2022)
In this modern era, people can easily get information from anywhere and anytime. People can also express their opinions and thoughts about a topic, for example about jokes. There are so many genres or types of jokes, one of them is dark jokes. Dark joke is a form of humor involving a twist or joke making the joke seen as offensive, harsh, horrid. Because of that, some people argue that dark jokes should not be used in daily life. The aim of this research is to analyze the students’ perception about using dark jokes in daily conversation English Department of Universitas Bandar Lampung and analyze some aspects of perception that affect students’ perception about using dark jokes in daily conversation. This research used case study method. The research was done at English Education Study Program Faculty of Teacher Training and Education Universitas Bandar Lampung in all semester. Data gathering was done by doing questionnaire and interview to nine students. The data was analyzed by combining the result from the questionnaire and interview. The results of this research elucidated that they have mix perception towards dark joke and using it in daily conversation. Some of them concur and some of them disagree that dark joke can be used in daily conversation.